The Influence of Tourist Attractions and Café Service Quality on Revisit Intention in Tanjung Duriat, Sumedang - Anastasya Putri Ardiyanto; M. Maulana; Irena Novarlia (Universitas Muhammadiyah Pontianak, 2026)
This study aims to examine the influence of tourist attractions and the quality of café services in Tanjung Duriat, Sumedang on interest in returning visits. The study used a quantitative correlation method using the purposive sampling technique and the Taro Yamane formula with a sample of 399 respondents. A Likert scale questionnaire was used to collect data, which was analyzed using validity, reliability, descriptive statistics, multiple linear regression, and hypothesis tests with IBM SPSS version 25. The results of the study show that partially or simultaneously, tourist attractions and the quality of café services have a positive and significant influence on interest in revisiting. This research indicates that strengthening tourist attractions and improving the quality of café services can increase loyalty and attract tourists to return to visit.